Central NPY‐Y5 sub‐receptor partially functions as a mediator of NPY‐induced hypothermia and affords thermotolerance in heat‐exposed fasted chicks. Issue 23 (6th December 2017) - Eltahan, Hatem M.; Bahry, Mohammad A.; Yang, Hui; Han, Guofeng; Nguyen, Linh T. N.; Ikeda, Hiromi; Ali, Mohamed N.; Amber, Khairy A.; Furuse, Mitsuhiro; Chowdhury, Vishwajit S.
Abstract: Exposure of chicks to a high ambient temperature (HT) has previously been shown to increase neuropeptide Y (NPY) mRNA expression in the brain. Furthermore, it was found that NPY has anti‐stress functions in heat‐exposed fasted chicks. The aim of the study was to reveal the role of central administration of NPY on thermotolerance ability and the induction of heat‐shock protein (HSP) and NPY sub‐receptors (NPYSRs) in fasted chicks with the contribution of plasma metabolite changes. Six‐ or seven‐day‐old chicks were centrally injected with 0 or 375 pmol of NPY and exposed to either HT (35 ± 1°C) or control thermoneutral temperature (CT: 30 ± 1°C) for 60 min while fasted. NPY reduced body temperature under both CT and HT. NPY enhanced the brain mRNA expression of HSP‐70 and ‐90, as well as of NPYSRs‐Y5, ‐Y6, and ‐Y7, but not ‐Y1, ‐Y2, and ‐Y4, under CT and HT. A coinjection of an NPYSR‐Y5 antagonist (CGP71683) and NPY (375 pmol) attenuated the NPY‐induced hypothermia. Furthermore, central NPY decreased plasma glucose and triacylglycerol under CT and HT and kept plasma corticosterone and epinephrine lower under HT. NPY increased plasma taurine and anserine concentrations. In conclusion, brain NPYSR‐Y5 partially afforded protective thermotolerance in heat‐exposed fasted chicks. The NPY‐mediated reduction in plasma glucose and stress hormone levels and the increase in free amino acids in plasma further suggest that NPY might potentially play a role in minimizing heat stress in fasted chicks. Abstract : Brain NPY sub‐receptor‐Y5 partially afforded protective thermotolerance in heat‐exposed fasted chicks. The NPY‐mediated reduction in plasma glucose and stress hormone levels and the increase in free amino acids in plasma further suggest that NPY might potentially play a role in minimizing heat stress in fasted chicks.